FEATURES OF THE ORIGIN OF FATTY LIVER DYSTROPHY IN ADOLESCENTS - Ahmedova N.A., Abdiyeva M.B., Oydinova M.O., Muzaffarov O.M.; Muzaffarova N.M. (Central Asian Journal of Medicine, 2025)
In this article, the influence of clinical-metabolic risk factors on the development of fatty hepatosis and the role of this disease in the deepening of obesity in the conditions of simple (exogenous-constitutional) obesity in 93 adolescents aged 17-30 years were determined. According to the results of the study, it was determined that abdominal obesity, insulin resistance, and stress are the most sensitive risk factors for the development of fatty hepatosis in adolescents. However, high specific risk factors include atherogenic dyslipidemia, hypertriglyceridemia, insulin resistance, inflammatory and prothrombotic conditions, and microalbuminuria. The frequency of fatty hepatosis among teenagers was 22%. We found out that the causes of fatty hepatosis in this age group are lack of energy, poor nutrition, and high consumption of energy products. Thus, taking into account the individual risk factors of adolescents in the early stages of fatty hepatosis, it is recommended to include drugs with hypolipidemic and hepatoprotective properties in the complex therapy for the prevention of fatty hepatosis.